Mitigating aflatoxin contamination in maize: Breeding for stable resistant cultivars - Oppong, Allen; Appiah Jnr, Kofi; Appiah-Kubi, Zippora; Adu-Amoah, Richard; Adu-Dapaah, Hans (Frontiers in Horticulture, 2022)
Maize is a major cereal crop for humans and animals. The production and consumption of maize are adversely affected by aflatoxin contamination resulting in reduced grain quality with high health risk to consumers. Unsafe aflatoxin levels above 20 ppb have been reported in maize from farmers’ fields in Ghana. A study was undertaken to evaluate the yield and aflatoxin contamination resistance stabilities of selected hybrids being developed in Ghana. Eighteen maize genotypes (14 hybrids with the following code names: GH01, GH02, GH03, GH04, GH05, GH06, GH07, GH08, GH09, GH10, GH11, GH12, GH13, and GH14 and four local checks: Etubi, Obotantim, Tintim, and Mamaba) were evaluated across six environments in two seasons. Artificial inoculation was done randomly using the side needle injection method 14 days after midsilk at a concentration of 9 × 107 conidia/ml. After the harvest levels of aflatoxin in the harvested grains were determined using high-performance liquid chromatography (HPLC). Data analysis showed that genotypic effects and environmental effects on some traits were consistently significant across environments, which mean that there was useful variation among the genotypes that could be utilized for the development of hybrids. Non-significant genotype by environment interaction effects for grain yield suggests that a promising genotype selected in one of these locations will also be suitable for production in the other locations in the same agroecological zone. GGE biplot analyses provided clear bases for determining stability and performance of the hybrids. Two hybrids have the potential for production in Ejura, Fumesua, Ohawu, Akumadan, and Kpeve and similar agroecological zones. GH04, GH10, and GH01 were lowest yielding, but GH10 was most stable. GH05 was identified as the most promising for production in Ejura, Ohawu, and Akumadan. Again, GH08 was the Vertex genotype for Wenchi environment. Ejura, located in the transition zone, was identified as the ideal testing environment for the hybrids. Most of the hybrids showed low levels of aflatoxin accumulation below 20 ppb despite artificial inoculation. The study revealed GH01, GH05, and GH08 as the most stable among the top yielding hybrids with aflatoxin levels of 11.9, 14.3, and 3.8 ppb, respectively, after artificial inoculation, which can be considered for cultivation as varieties to help mitigate aflatoxin contamination in maize in Ghana and beyond.